MUTATIONS DES ÉQUIPEMENTS DANS LES QUARTIERS PRÉCAIRES DE ZOÉ BRUNO, JEAN FOLLY ET SAGBÉ À ABIDJAN (CÔTE D’IVOIRE) - Koffi, Atta; Tere, Gogbe; Moussa, Kone (European Scientific Journal, ESJ, 2015)
Poor control of population growth in Côte d’Ivoire has resulted in the birth of precarious neighborhoods in the urban landscape. Abidjan, the economic capital is a perfect illustration. Under the leadership of the World Bank from 1980, these neighborhoods that were being destroyed are now being restructured and equipment. Because of this tolerance, more mutations are made through these neighborhoods. This is the case of precarious neighborhoods Zoe Bruno, Jean Folly and Sagbé space of our study. The objective of this study is to analyze the changes operated at the equipment level of these neighborhoods. To conduct the study, we used the hypothetical- deductive method to conduct research both exploratory and descriptive approach combining quantitative and qualitative. The surveys were conducted with 463 individuals including 450 households and 13 resource persons. This study showed destitution precarious neighborhoods studied in basic equipment and shows the various changes made in these neighborhoods after their regularization.